Effect Of Asset Management Efficiency On Performance Of Building And Construction Companies In Nigeria - Akparhuere, Godwin Oghenekohwo; Anastesia , Duru Nwakaego; Moses , Ogbu (Archives of Business Research, 2019)
The efficiency of asset management for various reasons has been the focus of companies, managers and investors doing building and construction business in Nigeria. The main objective of this study was to ascertain the effect of asset management efficiency on corporate performance of building and construction companies in Nigeria. To accomplish the main objective three specific objectives were formulated. These include examining the effects of asset turnover, inventory turnover and working capital turnover on profit after tax (proxy for performance). The study adopted the ex-post facto research design and secondary data were collected on the independent and dependent variables for ten (12) years, i.e. 2006-2017. The data were analyzed using simple regression method and it was found that net asset turnover and working capital turnover did not have significant effect on performance of building and construction companies in Nigeria. On the other hand, inventory turnover had significant effect on corporate performance of building and construction companies of Nigeria. It was recommended that management of building and construction companies should among other things adopt modern techniques of asset management that would translate asset turnover to corporate performance.